STUDY OF NON-SYMMETRICAL MODES OF THREE-PHASE FOUR-WIRE NETWORKS WITH DISTRIBUTED GENERATION - SINCHUK, Igor; KOTIAKOVA, Maryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The use of distributed generation electric energy sources allows efficient use of energy resources, including available renewable energy sources, contributes to the reduction of harmful emissions during traditional electric energy generation, improves the quality of electric energy for consumers and reduces overloading of transmission lines. Meanwhile, if the load supplied by the source of distributed generation is asymmetrical, then the voltage at the zero point of the inverter interface feeding the neutral conductor can deviate quite noticeably from the set level. The easiest way to provide a neutral point for connecting the neutral conductor is to use two capacitors with balancing resistors connected in parallel to them, that is, to create a zero voltage by dividing the total voltage of the direct current link in half. Circuits with voltage separation in the direct current circuit are widely used in electric drives with three-level energy converters, since in this case there is no need to connect the zero point of the direction to the load, and the main purpose of this electrical circuit is to obtain equal halves of the total voltage in the direct current circuit. This will lead to asymmetry of the output voltage, that is, to a decrease in its quality, the presence of significant constant components in alternating voltages, as well as to the flow of a significant current in the neutral conductor. In this regard, a three-dimensional space-vector pulse-width modulation method was proposed for controlling a four-arm inverter, which differs from the existing ones by the possibility of minimizing the components of negative and zero-sequence voltages in networks with distributed generation with parallel connection of three- and four-arm inverters . To develop approaches to control the inverters of such systems, it is necessary to obtain analytical dependencies that describe the flow of active and reactive power between inverters depending on the parameters of their generated output voltages.
Keywords: distributed generation; asymmetric modes; four-wire networks; electrical network; pulse width modulation